Sociological contributions to sustainable rural development: An integrative review of the literature (Research, Society and Development, 2021)
This research, by means of integrative revision, has as its objective to analyze the Brazilian scientific production which debates the understanding of Sustainable Development’s logics supported by sociology studies and research and to verify whether the rural scope is contemplated within those studies. Thorough research was conducted in Web of Science’s base and thus 19 papers were selected. Year of publication, language, source and type of document, research area and key words are analyzed. Two large themes were identified in the recovered papers, those being: Public Policies associated with Rural Sustainable Development and Management Practices associated with sustainable rural development making evident how studies in sociology comprehend this theme. In Brazil, the Amazon region has emphasis in the recovered studies, directed at projects and public policies directed at sustainable development. The interest in studies in this region of Brazil only reinforces its importance to the country’s sustainability.